Siglec10—An immunosuppressor and negative predictor of survival prognosis in gliomas - Wang, Hesong; Feng, Yanyan; Zhang, Yuxiang; Wang, Ting; Xu, Heng; Zhi, Yuxing; Feng, Yuyin; Tian, Lichun; Yuan, Kai (Frontiers in Genetics, 2022)
Glioma is a type of tumor occurring in the central nervous system. In recent decades, specific gene mutations and molecular aberrations are used to conduct glioma classification and clinical decisions. Siglec10 is a member of the sialic acid-binding immunoglobulin superfamily. In this study, we investigated the expression and functions of siglec10 in gliomas. We analyzed the siglec10 expression in glioma patients with immunohistochemical (IHC) staining and evaluated the survival prognosis. High siglec10 expression had a shorter survival prognosis than low siglec10 expression in patients, especially malignant gliomas. Bioinformatic datasets including TCGA and CGGA validated the IHC results and discovered the expression of siglec10 was higher in malignant subtype than a benign subtype of gliomas. So, siglec10 contributes to the poor prognosis of gliomas Furthermore, the related mechanisms of siglec10 in gliomas were investigated by functional enrichment analysis, including GSEA, GO, and KEGG analysis. Siglec10 was correlated with inflammatory mediators, inflammatory cells, and inflammatory pathways in gliomas. Siglec10 might take part in the immune response in the tumor microenvironment to induce glioma's progression and metastasis. This study showed siglec10 was a biomarker in glioma, and it might be the potential target of glioma immunotherapy in the future.